2017
DOI: 10.1111/rec.12635
|View full text |Cite
|
Sign up to set email alerts
|

Temporary grazing exclusion promotes rapid recovery of species richness and productivity in a long‐term overgrazed Campos grassland

Abstract: Moderate grazing intensity is considered the basic requirement to enhance ecosystem function in grasslands. Yet, deterioration by overgrazing is common in many biomes, including Campos grasslands in South America. Understanding how grazing management can lead to recovery of ecosystem function is essential to design and implement effective strategies for sustainable use of this resource. In a long‐term field experiment carried out in Southern Brazil, we studied the effects of temporal grazing exclusions (spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 41 publications
6
54
2
2
Order By: Relevance
“…The resilience of tropical old‐growth grasslands to human‐altered grazing and fire regimes is highly dependent on ecosystem type and site‐specific conditions. In general, disturbance‐dependent grasslands, with moderate to high soil water and nutrient availability, can tolerate more intense grazing for longer durations (Müller et al ., ; Fedrigo et al ., ) relative to edaphic grasslands, where soil conditions severely constrain plant productivity and regeneration (Kolbek & Alves, ; Fig. A, B).…”
Section: Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…The resilience of tropical old‐growth grasslands to human‐altered grazing and fire regimes is highly dependent on ecosystem type and site‐specific conditions. In general, disturbance‐dependent grasslands, with moderate to high soil water and nutrient availability, can tolerate more intense grazing for longer durations (Müller et al ., ; Fedrigo et al ., ) relative to edaphic grasslands, where soil conditions severely constrain plant productivity and regeneration (Kolbek & Alves, ; Fig. A, B).…”
Section: Resiliencementioning
confidence: 99%
“…One cannot substitute native wildlife for livestock and expect to maintain the same ecological processes and plant communities; grazing and browsing patterns differ among species and may change fire regimes, woody plant cover, and biogeochemical cycling (Hempson, Archibald & Bond, 2017). Whereas livestock are incompatible with conservation of edaphic old-growth grasslands, in certain disturbance-dependent old-growth grasslands, native wildlife and/or livestock can be used to manage vegetation if manipulated adequately (Fuhlendorf & Engle, 2001;Joubert, Pryke & Samways, 2017;Fedrigo et al, 2018). Further, where land-use policies restrict fire in disturbance-dependent grasslands, domestic livestock can, in some cases, serve as an imperfect surrogate for fire, by controlling the biomass of palatable dominant plants (both native or exotic) and preventing shrub and tree encroachment (Ratter et al, 1997;Müller et al, 2012).…”
Section: (3) Grazing Managementmentioning
confidence: 99%
“…; Fedrigo et al . ), this study could not dissociate the effects of grazing from other factors operating at larger spatial scales (i.e. rainfall).…”
Section: Discussionmentioning
confidence: 89%
“…Although grazing rest during periods of peak plant growth and reproduction (i.e. spring) has been shown to maintain native forb richness and grass cover (Leonard & Kirkpatrick 2004;Zimmer et al 2010b;Mavromihalis et al 2013;Fedrigo et al 2018), this study could not dissociate the effects of grazing from other factors operating at larger spatial scales (i.e. rainfall).…”
Section: Discussionmentioning
confidence: 91%
“…We based this assumption on our field experience of more than 20 years (C. S. Fontana) as well as on the results of studies indicating that plant species richness (Torchelsen et al ) and floristic composition of grassland remnants (Fensham et al ) can recover within ~ 10 years of abandonment, even if some differences to reference grasslands may remain both in terms of structure and floristic composition (Tognetti et al ). In addition, Fedrigo et al () evaluated the vegetation of Pampa grasslands and found high restoration capacity within ~ 3 months after a long period of intense grazing.…”
Section: Methodsmentioning
confidence: 99%